Kajian Identifikasi dan Dominansi Gulma pada Areal Pertanaman Kelapa di Dusun Hulung Kabupaten Maluku Tengah - Harianja, Hanya Sari; Tanasale, Vilma Laurien; Riry, Johan (JURNAL PERTANIAN KEPULAUAN, 2024)
Coconut crop production cannot be maintained and tends to decline. This research aims to identify types of weeds and find the dominant weed types in coconut planting areas. This research was carried out in a coconut farming area in Hulung in May 2024. The tools used in this research were a camera, a frame measuring 1x1 m, a cutter, an oven, analytical scales, a handheld, and an analytical balance manual. This research uses the vegetation survey method to collect data by field observations. In carrying out the vegetation analysis, the quadratic method was used by placing sample plots measuring 1m x 1m on 6 trees randomly. From the results of observing weeds in Hulung village, it shows that in the coconut plantation area, there are 20 types of weeds, 14 types of broadleaf weeds, 3 types of fern weeds, 2 types of grass weeds and 1 type of grass weed.The weeds Digitaria cilliaris, Commelina diffusa burn, Digitarius sanguinalis and weeds and Sphagneticola trilobata L) have high SDR values ​​compared to other types of weeds. The dominant weed types in the coconut plantation area in Hulung Hamlet are the grass weed Digitaria ciliaris and broadleaf weed types. Annual weeds dominate coconut plantation areas.